2016
DOI: 10.1016/j.molimm.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Complement MASP-1 enhances adhesion between endothelial cells and neutrophils by up-regulating E‐selectin expression

Abstract: Abbreviation: HUVEC, human umbilical vein endothelial cell; MBL, mannan-binding lectin; MASP, mannan-binding lectin-associated serine protease; PAR, protease-activated receptor. AbstractThe complement system and neutrophil granulocytes are indispensable in the immune response against extracellular pathogens such as bacteria and fungi. Endothelial cells also participate in antimicrobial immunity largely by regulating the homing of leukocytes through their cytokine production and their pattern of cell surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 50 publications
3
37
0
Order By: Relevance
“…Other immune‐related genes were expressed at lower levels in the liver of congenic mice compared with those in the mixed background (Fig. B), such as hepcidin ( Hamp ), a peptide with bactericidal activity against E. coli ; scavenger receptor A5 ( Scara5 ) and toll‐like receptor 5 ( Tlr5 ), which both participate in the clearance of bacteria; Mannan‐binding lectin‐associated serine protease‐1 ( Masp‐1 ), a complement lectin pathway enzyme that enhances the antimicrobial immune response; Chitinase 3‐Like 1 ( Chil1 ), a protein increased in the circulation during E. coli endotoxemia, which promotes host resistance and tolerance to bacteria; or tumor necrosis factor receptor superfamily, member 14 ( Tnfrsf14 ), a susceptibility loci for primary sclerosing cholangitis, critical for the development of protective mucosal CD8 T‐cell memory . Sushi domain‐containing protein 4 ( Susd4 ), a complement inhibitor that presumably limits beneficial complement activation (e.g., in pathogens removal) to the local site, was also underexpressed by more than 58‐fold in the liver of congenic mice.…”
Section: Resultsmentioning
confidence: 99%
“…Other immune‐related genes were expressed at lower levels in the liver of congenic mice compared with those in the mixed background (Fig. B), such as hepcidin ( Hamp ), a peptide with bactericidal activity against E. coli ; scavenger receptor A5 ( Scara5 ) and toll‐like receptor 5 ( Tlr5 ), which both participate in the clearance of bacteria; Mannan‐binding lectin‐associated serine protease‐1 ( Masp‐1 ), a complement lectin pathway enzyme that enhances the antimicrobial immune response; Chitinase 3‐Like 1 ( Chil1 ), a protein increased in the circulation during E. coli endotoxemia, which promotes host resistance and tolerance to bacteria; or tumor necrosis factor receptor superfamily, member 14 ( Tnfrsf14 ), a susceptibility loci for primary sclerosing cholangitis, critical for the development of protective mucosal CD8 T‐cell memory . Sushi domain‐containing protein 4 ( Susd4 ), a complement inhibitor that presumably limits beneficial complement activation (e.g., in pathogens removal) to the local site, was also underexpressed by more than 58‐fold in the liver of congenic mice.…”
Section: Resultsmentioning
confidence: 99%
“…Adhesion force between individual human white blood cells and specific macromolecules were studied with the technique [124], [125], [126].…”
Section: Computer-controlled Micropipettementioning
confidence: 99%
“…Hundreds of cells: total number of human immune cells probed by the micropipette was 200-600 [23] 0-2 µN [23] ~30 min [23] * Relatively high throughput [23], especially when compared to AFM or FluidFM * Direct visualization of cells [23] * Higher sensitivity and less side-effect than in microfluidic shear stress channel [23] * Hydrodynamic simulations are needed to convert the experimental vacuum value to hydrodynamic lifting force [23] * Probing single cell interactions with specific macromolecules [23] * Studying cell-cell interactions [124] Method a) Manipulations of a cell takes less than 15 min [133] * Extreme force sensitivity down to 0.1 pN [127], [130] * High spatial resolution (0.1-2 nm) [130] * Contactless force for manipulations [127] * The range of applied forces is limited to max. 100 pN [130] * Photodamage and thermal damage [127], [135] * Interaction and binding assays [130], [132], [141], [142], [143], [144], [226] * Tethered assay [127], [132], [145], [146] [163], [164], [165] *AFM-based SCFS: 5 pN-100 nN [149] * Chemical functionalization of the cantilever: 1h * ~10 min needed for proper cellcantilever interaction * Relatively short contact times (msec-20min) [43], [170] * Spatial and force resolution is high [148] * pN force sensitivity *nm positioning accuracy * Can map and analyze individual receptors with nanoscale lateral resolution [148] * Costly method <...>…”
Section: Computer Controlled Micropipettementioning
confidence: 99%
“…We showed that MASP‐1 (similarly to thrombin) can cleave protease‐activated receptors (PARs) on the surface of endothelial cells, which results in the pro‐inflammatory activation of endothelial cells . Activation of p38 MAPK, pCREB, NFκB, and JNK pathways along with Ca mobilization led to cytokine production and altered adhesion molecule pattern in a HUVEC model . Elevated IL‐8 secretion and E‐selectin expression resulted in increased neutrophil chemotaxis and adhesion forces toward endothelial cells.…”
Section: The Role Of Masps In Cell Activationmentioning
confidence: 99%
“…81 Activation of p38 MAPK, pCREB, NFκB, and JNK pathways along with Ca mobilization led to cytokine production and altered adhesion molecule pattern in a HUVEC model. 82,83 Elevated IL-8 secretion and E-selectin expression resulted in increased neutrophil chemotaxis and adhesion forces toward endothelial cells.…”
Section: Masp-1 Activates Endothelial Cells Through Par Cleavagementioning
confidence: 99%